A bibliometric analysis of dance education’s impact on children’s social skills and physical health - Yang, Mengzhuo; Koh, Denise (Edelweiss Applied Science and Technology, 2025)
This study presents a comprehensive bibliometric analysis of dance education research from 2003 to 2024, focusing on its implications for children’s physical development and social skills. Drawing on 622 publications indexed in the Web of Science database, the research employs CiteSpace 6.1 to map knowledge structures, identify influential authors, institutions, and countries, and analyze keyword co-occurrence and citation bursts. The findings highlight a growing scholarly interest in dance education, with significant contributions from the United States, Brazil, and the United Kingdom. Notably, keywords such as “children,” “physical activity,” and “health” dominate the discourse, reflecting the field’s emphasis on developmental outcomes. Co-authorship and institutional network analyses reveal strong collaborative patterns, particularly involving researchers like Caroline Brand and institutions such as the Universidade Federal do Rio Grande do Sul. The study underscores dance education’s multifaceted role in promoting motor coordination, emotional regulation, and social competencies. It also identifies research gaps, including the need for longitudinal studies and greater integration of technology-enhanced dance interventions. This analysis provides a visual and data-driven foundation for future investigations and policy-making in dance education and child development.